PELAKSANAAN SUPERMIK PINTER UNTUK MENINGKATKAN KOMPETENSI GURU DALAM MENYUSUN RENCANA PELAKSANAAN PEMBELAJARAN BERBASIS KURIKULUM 2013 DI SMP BINAAN KOTA DUMAI - Yusnida Yusnida (JURNAL PAJAR (Pendidikan dan Pengajaran), 2019)
Based on the problems faced by teachers in the preparation of the 2013 curriculum-based lesson plans, the purpose of this study is to improve the competence of teachers in preparing 2013 curriculum-based lesson plans by implementing supermic pinter. The design of this study used school action research conducted on 6 chemistry teachers in the target schools in Dumai. The results showed that the implementation of supermic pinter can improve teacher competence in preparing 2013 curriculum-based lesson plans, where in the first cycle the percentage of teacher competence was 60% with sufficient categories and increased to 84% with a very good category in cycle II. Based on the results of the study it can be concluded that the implementation of smart supermic can improve the competence of teachers in preparing plans for the implementation of 2013 curriculum-based learning in the Dumai City-assisted Middle School.